Effect of topical application of methylsulfonylmethane (MSM), EDTA on pitting edema and oxidative stress in a double blind, placebo-controlled study - Tripathi, R.; Gupta, S.; Rai, S.; Mittal, P. C. (Cellular and Molecular Biology, 2011)
No pharmacological treatment exists for lower extremity pitting edema, characterized by inflammation, found in chronic venous insufficiency. Treatment with EDTA, an effective metal chelator, was explored because it can modulate free calcium and iron and prevent further free radical production. However, EDTA may not effectively penetrate the cell membrane, hence methylsulfonylmethane(MSM), reported to facilitate transmembrane transport, was added. The effect of topical application of a lotion containing MSM+EDTA was assessed in two phases of a double blind, placebo controlled clinical trial. In phase 1, patients having swelling in the lower extremities were randomly distributed to receive the MSM+EDTA lotion or a placebo (vehicle) alone. In the second phase, patients were given MSM as placebo followed by MSM+EDTA lotion for 2 weeks. The circumference of calf, ankle and foot for both legs were found to decline significantly after 2 weeks of application of the lotion/ but not placebo, and total antioxidant capacity (FRAP) and lipid peroxidation products (MDA), assayed in blood, showed decline in oxidative stress. Application of MSM alone increased the swelling. Thus EDTA+MSM offers an efficacious treatment for lower extremity pitting edema, through reduction in oxidative stress.